Budget allocation design in the EU pre-commercial procurement for innovation. Issue 1 (29th January 2020) - Dimitri, Nicola
Abstract : Purpose: Pre-commercial procurement (PCP), introduced by the European Commission in 2007, is the most important purchasing procedure available to the European Union public sector to solicit innovative solutions from the business sector. As such solutions are not yet in the market, they first require research and development (R&D) activities. PCP is concerned with procuring R&D services only, and typically consists of three phases. This paper aims to discuss how the budget available to the contracting authority (CA) may be optimally allocated along such three phases. Design/methodology/approach: The paper is mostly theoretical and the CA is assumed to maximise the overall probability of success in the PCP, that is the probability of receiving at least one successful proposal at the end of the procedure. Findings: The main finding of the paper suggests that, for a CA, the optimal budget allocation across the three phases of the PCP depends on how likely it is to receive successful proposals in various stages of the procedure, as well as on the rewards paid to the invited companies. Practical implications: In this paper, the author proposes a methodology for the optimal budget allocation of a CA and discusses how the approach could be practically implemented, pointing out its potential difficulties. Social implications: The main social implication of the findings is represented by the best use of the available budget, hence taxpayers' money. Originality/value: To the best of the author's knowledge, no existing paper has discussed the optimal budget allocation in a PCP as in this work.